Implementasi Tari Pendidikan dalam Kurikulum Sekolah Dasar untuk Mencapai Pendidikan Berkualitas - Dwi SP Pratama; Hartono Hartono (Tambuleng, 2026)
This study aims to analyze the implementation of dance education in the elementary school curriculum (SD) as a strategy for achieving quality education. The method used is literature review. The author has reviewed 10 articles from nationally accredited and internationally reputable journals in the range of 2020-2026. The results showed that dance education has been effectively integrated through three main models: (1) local content of Dance, (2) the theme of movement in thematic learning, and (3) character-based extracurricular. Such implementation contributes to the development of fine and gross motor, kinesthetic intelligence, as well as the values of discipline and cooperation. However, the main obstacles faced by elementary school teachers include lack of training in dance pedagogy and limited time allocation. The recommendations of this study include the need for the development of integrated teaching modules and sustainable professional development programs for elementary school teachers. Thus, dance education can be recommended as an innovative approach to realizing quality education (SDG 4).